2001
DOI: 10.1109/78.934150
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic properties of the algebraic constant modulus algorithm

Abstract: Abstract-The algebraic constant modulus algorithm (ACMA) is a noniterative blind source separation algorithm. It computes jointly beamforming vectors for all constant modulus sources as the solution of a joint diagonalization problem. In this paper, we analyze its asymptotic properties and show that (unlike CMA) it converges to the Wiener beamformer when the number of samples or the signal-to-noise ratio (SNR) goes to infinity. We also sketch its connection to the related JADE algorithm and derive a version of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 33 publications
1
58
0
Order By: Relevance
“…The study of in Appendix II comes to the conclusion that the Gaussian assumption is optimal at high SNR unless some eigenvalues of the kurtosis matrix are equal to 1. This condition is closely related to the constant modulus property of the nuisance parameters [13]. To validate this result, let us obtain the asymptotic expression of (10) as the noise variance goes to zero .…”
Section: Best Quadratic Unbiased Estimatormentioning
confidence: 99%
See 4 more Smart Citations
“…The study of in Appendix II comes to the conclusion that the Gaussian assumption is optimal at high SNR unless some eigenvalues of the kurtosis matrix are equal to 1. This condition is closely related to the constant modulus property of the nuisance parameters [13]. To validate this result, let us obtain the asymptotic expression of (10) as the noise variance goes to zero .…”
Section: Best Quadratic Unbiased Estimatormentioning
confidence: 99%
“…The kurtosis matrix is null in the Gaussian case and provides the complete non-Gaussian information on the nuisance parameters that second-order NDA estimators are able to exploit [8]. In case of circular complex nuisance parameters, is given by the following diagonal matrix: (6) where is the fourth-order moment of the nuisance parameters [8], [13]. It can be shown that for PSK constellations [13], for QAM and APSK constellations and in the Gaussian case.…”
Section: Non-gaussian Nuisance Parametersmentioning
confidence: 99%
See 3 more Smart Citations